Skip to content
🎉 DeepSeek-R1 🥳
There are three piles containing 22, 14, and 12 nuts. It is necessary to equalize the number of nuts in all piles by making three moves, while adhering to the following condition: it is only allowed to move as many nuts from one pile to another as there are in the pile to which the nuts are being moved.

💡Alright, so I've got this problem here about three piles of nuts. The piles have 22, 14, and 12 nuts respectively. The goal is to make all three piles have the same number of nuts, but I can only do this by moving nuts between the piles in a specific way. The rule is that I can only move as many nuts from one pile to another as there are in the destination pile. And I have to do this in three moves. Hmm, okay, let's break this down.First, I need to understand the rule clearly. If I'm moving nuts from pile A to pile B, I can only move as many nuts as are currently in pile B. So, if pile B has 10 nuts, I can move 10 nuts from pile A to pile B. That means the number of nuts I can move is directly tied to the size of the destination pile at the time of the move. Got it.Now, the total number of nuts across all three piles is 22 + 14 + 12, which is 48 nuts. If I want to equalize the piles, each pile should have 48 divided by 3, which is 16 nuts. So, the target is to have 16 nuts in each pile.Starting with the piles at 22, 14, and 12, I need to figure out how to redistribute these nuts in three moves. Let's think about the first move. Since I can only move as many nuts as are in the destination pile, I need to decide which pile to move nuts to and from.Maybe I should start by moving nuts from the largest pile to one of the smaller ones. The largest pile has 22 nuts, and the smaller piles have 14 and 12. If I move nuts from the 22 pile to the 14 pile, I can move up to 14 nuts. That would leave the 22 pile with 8 nuts and the 14 pile would become 28 nuts. So after the first move, the piles would be 8, 28, and 12.Okay, that seems like a good start. Now, for the second move, I need to decide where to move nuts next. The piles are now 8, 28, and 12. The largest pile is now 28, and the smallest is 8. Maybe I should move nuts from the 28 pile to the 12 pile. Since the destination pile has 12 nuts, I can move 12 nuts from the 28 pile to the 12 pile. That would leave the 28 pile with 16 nuts and the 12 pile would become 24 nuts. So now the piles are 8, 16, and 24.Alright, now for the third move. The piles are 8, 16, and 24. The largest pile is 24, and the smallest is 8. I need to move nuts from the 24 pile to the 8 pile. Since the destination pile has 8 nuts, I can move 8 nuts from the 24 pile to the 8 pile. That would leave the 24 pile with 16 nuts and the 8 pile would become 16 nuts. So now all piles have 16 nuts each.Wait, that worked out perfectly in three moves. Let me just recap:1. Move 14 nuts from the 22 pile to the 14 pile, resulting in 8, 28, and 12.2. Move 12 nuts from the 28 pile to the 12 pile, resulting in 8, 16, and 24.3. Move 8 nuts from the 24 pile to the 8 pile, resulting in 16, 16, and 16.Yeah, that seems to do it. Each move adheres to the rule of moving as many nuts as are in the destination pile, and it only took three moves to equalize all piles.I wonder if there's another way to do it, maybe starting with a different move. Let's see. Suppose I first move nuts from the 22 pile to the 12 pile instead. Since the destination pile has 12 nuts, I can move 12 nuts from the 22 pile to the 12 pile. That would leave the 22 pile with 10 nuts and the 12 pile would become 24 nuts. So now the piles are 10, 14, and 24.Next, I might move nuts from the 24 pile to the 14 pile. The destination pile has 14 nuts, so I can move 14 nuts from the 24 pile to the 14 pile. That would leave the 24 pile with 10 nuts and the 14 pile would become 28 nuts. Now the piles are 10, 28, and 10.For the third move, I need to move nuts from the 28 pile to one of the 10 piles. Let's say I move 10 nuts from the 28 pile to one of the 10 piles. That would leave the 28 pile with 18 nuts and the destination pile would become 20 nuts. Now the piles are 20, 18, and 10.Hmm, that didn't work out. I ended up with unequal piles. Maybe I should have moved differently. Let's try moving from the 28 pile to the other 10 pile instead. So, moving 10 nuts from the 28 pile to the other 10 pile, resulting in 20, 18, and 20. Still unequal.Okay, so that approach didn't work. Maybe starting by moving from the 22 pile to the 12 pile isn't the best first move. Let's try another strategy.What if I first move nuts from the 14 pile to the 12 pile? The destination pile has 12 nuts, so I can move 12 nuts from the 14 pile to the 12 pile. That would leave the 14 pile with 2 nuts and the 12 pile would become 24 nuts. Now the piles are 22, 2, and 24.Next, I might move nuts from the 24 pile to the 2 pile. The destination pile has 2 nuts, so I can move 2 nuts from the 24 pile to the 2 pile. That would leave the 24 pile with 22 nuts and the 2 pile would become 4 nuts. Now the piles are 22, 4, and 22.For the third move, I need to move nuts from one of the 22 piles to the 4 pile. The destination pile has 4 nuts, so I can move 4 nuts from one of the 22 piles to the 4 pile. That would leave the 22 pile with 18 nuts and the 4 pile would become 8 nuts. Now the piles are 18, 8, and 22.Still unequal. Hmm, this isn't working either. Maybe moving from the 14 pile to the 12 pile isn't the right first move.Let me go back to my initial approach, which worked. Moving from the largest pile to the next largest pile first seems to be the key. That way, I can balance the piles more effectively.So, first move: 14 nuts from 22 to 14, resulting in 8, 28, 12.Second move: 12 nuts from 28 to 12, resulting in 8, 16, 24.Third move: 8 nuts from 24 to 8, resulting in 16, 16, 16.Yes, that works perfectly. I think that's the most efficient way to do it.I wonder if there's a mathematical way to represent this. Let's see. The total number of nuts is 48, so each pile should have 16. The initial piles are 22, 14, and 12. The differences from 16 are +6, -2, and -4.So, I need to transfer 6 nuts out of the first pile, and 2 and 4 nuts into the second and third piles respectively. But the transfers have to follow the rule of moving as many nuts as are in the destination pile.In the first move, moving 14 nuts from the first pile to the second pile, which has 14 nuts. That reduces the first pile by 14, making it 8, and increases the second pile by 14, making it 28. Now, the differences are -8, +12, and -4.Second move, moving 12 nuts from the second pile to the third pile, which has 12 nuts. That reduces the second pile by 12, making it 16, and increases the third pile by 12, making it 24. Now, the differences are -8, 0, +8.Third move, moving 8 nuts from the third pile to the first pile, which has 8 nuts. That reduces the third pile by 8, making it 16, and increases the first pile by 8, making it 16. Now, all piles have 16 nuts.This mathematical representation helps confirm that the moves are correct. Each move adjusts the piles towards the target of 16 nuts, following the rule.I think I've got it figured out. The key was to start by moving from the largest pile to the next largest, then to the smallest, and finally balancing the last transfer. It took some trial and error, but breaking it down step by step made it manageable.

An athlete's heart beats an average of 160 times per minute while running. How many times does the athlete's heart beat during a 30-mile race if the athlete runs at a pace of 6 minutes per mile?

💡Okay, so I have this problem here: An athlete's heart beats an average of 160 times per minute while running. I need to figure out how many times the athlete's heart beats during a 30-mile race if the athlete runs at a pace of 6 minutes per mile. Hmm, okay, let's break this down step by step.First, I need to understand what's being asked. The athlete is running a 30-mile race, and their heart rate is 160 beats per minute. They run at a pace of 6 minutes per mile. So, I need to find the total number of heartbeats during the entire race.Alright, to find the total number of heartbeats, I think I need to know how long the race takes in total. Once I have the total time, I can multiply that by the heart rate to get the total number of beats.So, the athlete is running 30 miles at a pace of 6 minutes per mile. That means for each mile, it takes them 6 minutes. To find the total time for the race, I should multiply the number of miles by the time per mile. Let me write that down:Total time = Number of miles × Time per mileTotal time = 30 miles × 6 minutes per mileOkay, doing that multiplication: 30 × 6 = 180 minutes. So, the race takes 180 minutes in total.Now that I have the total time, I can calculate the total number of heartbeats. The athlete's heart beats 160 times every minute. So, over 180 minutes, the total heartbeats would be:Total heartbeats = Heart rate × Total timeTotal heartbeats = 160 beats per minute × 180 minutesLet me calculate that: 160 × 180. Hmm, 160 × 100 is 16,000, and 160 × 80 is 12,800. Adding those together gives 16,000 + 12,800 = 28,800. So, the total number of heartbeats is 28,800.Wait, let me double-check that multiplication to make sure I didn't make a mistake. 160 × 180 can also be calculated as 160 × (200 - 20) = 160 × 200 - 160 × 20 = 32,000 - 3,200 = 28,800. Yep, that matches. So, the calculation seems correct.Just to recap, the steps I took were:1. Determine the total time taken to complete the race by multiplying the pace per mile by the number of miles.2. Multiply the total time by the heart rate to find the total number of heartbeats.Everything seems to add up, so I'm confident that the total number of heartbeats during the race is 28,800.

Prove that if a number in the decimal system is divided by (2^{n}) or (5^{n}) (where (n) is a natural number), the remainder will be the same as if the number formed by the last (n) digits of the original number is divided by (2^{n}) or (5^{n}), respectively.

💡Okay, so I have this problem to prove that if a number in the decimal system is divided by (2^n) or (5^n) (where (n) is a natural number), the remainder will be the same as if the number formed by the last (n) digits of the original number is divided by (2^n) or (5^n), respectively. Hmm, that sounds a bit abstract, but let me try to break it down.First, I need to recall some basic number theory concepts. I know that any number in the decimal system can be expressed as a sum of its digits multiplied by powers of 10. For example, a number like 1234 can be written as (1 times 10^3 + 2 times 10^2 + 3 times 10^1 + 4 times 10^0). So, in general, any number (N) can be written as:[N = a_k times 10^k + a_{k-1} times 10^{k-1} + ldots + a_1 times 10 + a_0]where (a_0, a_1, ldots, a_k) are the digits of the number.Now, the problem is about dividing this number by (2^n) or (5^n) and looking at the remainder. I remember that when dealing with remainders, modular arithmetic is really useful. Specifically, if I want to find (N mod 2^n) or (N mod 5^n), I can use properties of modular arithmetic to simplify the problem.Let me focus on (2^n) first. I know that (10 = 2 times 5), so (10^n = 2^n times 5^n). This means that (10^n) is divisible by both (2^n) and (5^n). Therefore, any multiple of (10^n) will be congruent to 0 modulo (2^n) and modulo (5^n). So, if I have a number (N) and I separate it into two parts: the part that is a multiple of (10^n) and the part that is less than (10^n), then when I take modulo (2^n) or (5^n), the multiple of (10^n) will vanish, leaving only the remainder from the last (n) digits.Let me write this more formally. Suppose (N) is a number with more than (n) digits. I can express (N) as:[N = 10^n times M + R]where (M) is the number formed by the digits of (N) excluding the last (n) digits, and (R) is the number formed by the last (n) digits of (N).Now, when I take (N mod 2^n), I get:[N mod 2^n = (10^n times M + R) mod 2^n]Since (10^n) is divisible by (2^n), (10^n times M mod 2^n = 0). Therefore:[N mod 2^n = R mod 2^n]Similarly, for (5^n):[N mod 5^n = (10^n times M + R) mod 5^n]Again, (10^n) is divisible by (5^n), so (10^n times M mod 5^n = 0). Thus:[N mod 5^n = R mod 5^n]This shows that the remainder when (N) is divided by (2^n) or (5^n) is the same as the remainder when the last (n) digits of (N) are divided by (2^n) or (5^n), respectively.Wait, but I should make sure that this holds for any natural number (n). Let me test it with a small example to verify.Let's take (n = 2). So, we're looking at the last two digits of a number. Let's pick a number, say, 123456. The last two digits are 56.First, let's compute (123456 mod 4) (since (2^2 = 4)):[123456 div 4 = 30864 text{ with a remainder of } 0]Now, let's compute (56 mod 4):[56 div 4 = 14 text{ with a remainder of } 0]Okay, same remainder.Now, let's compute (123456 mod 25) (since (5^2 = 25)):[123456 div 25 = 4938 text{ with a remainder of } 6]And (56 mod 25):[56 div 25 = 2 text{ with a remainder of } 6]Again, same remainder. So, it works for (n = 2).Let me try another example with (n = 3). Take the number 987654321. The last three digits are 4321? Wait, no, the last three digits are 321.Compute (987654321 mod 8) (since (2^3 = 8)):[987654321 div 8 = 123456790 text{ with a remainder of } 1]Now, (321 mod 8):[321 div 8 = 40 text{ with a remainder of } 1]Same remainder.Now, (987654321 mod 125) (since (5^3 = 125)):[987654321 div 125 = 7901234 text{ with a remainder of } 101]And (321 mod 125):[321 div 125 = 2 text{ with a remainder of } 71]Wait, that's different. Did I do something wrong? Let me check.Wait, no, I think I made a mistake in the last three digits. The number is 987654321, so the last three digits are 321, right? But when I compute (987654321 mod 125), I should get the same remainder as (321 mod 125). Let me recalculate.Compute (987654321 mod 125):First, note that (1000 mod 125 = 0), because (1000 = 8 times 125). So, any number can be broken down into chunks of 1000, and each chunk beyond the last three digits will be divisible by 125. Therefore, (987654321 mod 125 = 4321 mod 125). Wait, but I thought the last three digits were 321. Hmm, maybe I miscounted.Wait, 987654321 has 9 digits: 9 8 7 6 5 4 3 2 1. So, the last three digits are 3 2 1, which is 321. But when I compute (987654321 mod 125), I should get the same as (321 mod 125). Let's compute (321 mod 125):[321 div 125 = 2 times 125 = 250, text{ remainder } 71]Now, let's compute (987654321 mod 125):Since (1000 mod 125 = 0), we can write:[987654321 = 987 times 1000000 + 654 times 1000 + 321]Each (1000) term is divisible by 125, so modulo 125, this is equivalent to (321 mod 125 = 71). So, the remainder is indeed 71, which matches (321 mod 125). So, my initial calculation was correct.I think I confused myself earlier when I thought the remainder was 101, but actually, it's 71. So, it does hold for (n = 3) as well.Another example: Let's take (n = 1). So, we're looking at the last digit. Take the number 12345. The last digit is 5.Compute (12345 mod 2):[12345 div 2 = 6172 text{ with a remainder of } 1]And (5 mod 2 = 1). Same remainder.Compute (12345 mod 5):[12345 div 5 = 2469 text{ with a remainder of } 0]And (5 mod 5 = 0). Same remainder.Okay, so it works for (n = 1) as well.I think I have a good grasp now. The key idea is that (10^n) is divisible by both (2^n) and (5^n), so any higher place values beyond the last (n) digits don't affect the remainder when divided by (2^n) or (5^n). Therefore, only the last (n) digits contribute to the remainder.To formalize this, let me write it step by step.Given a number (N) in the decimal system, we can express it as:[N = a_k times 10^k + a_{k-1} times 10^{k-1} + ldots + a_n times 10^n + a_{n-1} times 10^{n-1} + ldots + a_1 times 10 + a_0]where (a_0, a_1, ldots, a_k) are digits (0-9).We can separate (N) into two parts:[N = 10^n times M + R]where (M = a_k times 10^{k-n} + a_{k-1} times 10^{k-n-1} + ldots + a_n) and (R = a_{n-1} times 10^{n-1} + ldots + a_1 times 10 + a_0).Now, consider (N mod 2^n):[N mod 2^n = (10^n times M + R) mod 2^n]Since (10^n = 2^n times 5^n), (10^n times M) is divisible by (2^n), so:[10^n times M mod 2^n = 0]Therefore:[N mod 2^n = R mod 2^n]Similarly, for (5^n):[N mod 5^n = (10^n times M + R) mod 5^n]Again, (10^n = 2^n times 5^n), so (10^n times M) is divisible by (5^n), hence:[10^n times M mod 5^n = 0]Thus:[N mod 5^n = R mod 5^n]This proves that the remainder when (N) is divided by (2^n) or (5^n) is the same as the remainder when the last (n) digits of (N) are divided by (2^n) or (5^n), respectively.I think this covers the proof comprehensively. I've tested it with examples and broken it down step by step, so I'm confident it's correct.

Calculate {(-frac{4}{5})^{2022}} times {(frac{5}{4})^{2023}}=____.

💡To solve the expression ({(-frac{4}{5})^{2022}} times {(frac{5}{4})^{2023}}), we can follow these steps:1. **Simplify the Negative Base:** Since the exponent 2022 is even, the negative sign in (-frac{4}{5}) will become positive. [ {(-frac{4}{5})^{2022}} = (frac{4}{5})^{2022} ]2. **Express the Second Term with a Common Base:** Notice that (frac{5}{4}) is the reciprocal of (frac{4}{5}). We can rewrite the second term to align with the first term's base. [ {(frac{5}{4})^{2023}} = {(frac{5}{4})^{2022}} times frac{5}{4} ]3. **Combine the Terms:** Multiply the simplified first term with the rewritten second term. [ (frac{4}{5})^{2022} times {(frac{5}{4})^{2022}} times frac{5}{4} ]4. **Simplify the Product of Powers:** When multiplying powers with the same exponent, we can combine the bases. [ (frac{4}{5} times frac{5}{4})^{2022} times frac{5}{4} ] [ 1^{2022} times frac{5}{4} ]5. **Final Simplification:** Since any number to the power of 1 is itself, we have: [ 1 times frac{5}{4} = frac{5}{4} ]

Determine the units digit of the quotient frac{4^{1985} + 7^{1985}}{7} given that 4^{1985} + 7^{1985} is a multiple of 7.

💡Okay, so I need to find the units digit of the quotient when (4^1985 + 7^1985) is divided by 7. The problem already tells me that 4^1985 + 7^1985 is a multiple of 7, so dividing it by 7 will give me an integer. My goal is to figure out what the units digit of that integer is.First, let me think about how to approach this. Since we're dealing with exponents, maybe I can find a pattern in the units digits of powers of 4 and 7. That might help me figure out what 4^1985 and 7^1985 are modulo 10, which would give me their units digits. Then, I can add those units digits together and see what the units digit of the sum is. After that, I can divide by 7 and find the units digit of the result.Wait, but actually, since we're dividing by 7, maybe it's better to work modulo 7 first to simplify the expression, and then figure out the units digit. Hmm, I'm not sure. Let me try both approaches and see which one works better.Starting with the first idea: finding the units digits of 4^1985 and 7^1985.For 4^n, the units digit cycles every 2:- 4^1 = 4 (units digit 4)- 4^2 = 16 (units digit 6)- 4^3 = 64 (units digit 4)- 4^4 = 256 (units digit 6)So the cycle is 4, 6, 4, 6, etc. Since 1985 is an odd number, 4^1985 will have a units digit of 4.For 7^n, the units digit cycles every 4:- 7^1 = 7 (units digit 7)- 7^2 = 49 (units digit 9)- 7^3 = 343 (units digit 3)- 7^4 = 2401 (units digit 1)- 7^5 = 16807 (units digit 7)So the cycle is 7, 9, 3, 1, and repeats every 4. Now, 1985 divided by 4 is 496 with a remainder of 1. So 7^1985 will have the same units digit as 7^1, which is 7.So, adding the units digits: 4 (from 4^1985) + 7 (from 7^1985) = 11. So the units digit of the sum 4^1985 + 7^1985 is 1.But wait, the problem says that 4^1985 + 7^1985 is a multiple of 7, so when we divide by 7, we need to find the units digit of the quotient. If the units digit of the numerator is 1, then dividing by 7... Hmm, this might not be straightforward because the units digit of the quotient isn't just the units digit of the numerator divided by 7. It depends on the entire number.Maybe I should approach this differently. Let's consider the expression modulo 70, since we're interested in the units digit (which is modulo 10) and we're dividing by 7. If I can find (4^1985 + 7^1985) modulo 70, then dividing by 7 will give me the result modulo 10, which is the units digit.So, let's compute 4^1985 modulo 70 and 7^1985 modulo 70.First, 4^1985 modulo 70. Since 70 = 7 * 10, and 4 and 70 are coprime, I can use Euler's theorem. Euler's totient function φ(70) = φ(7*10) = φ(7)*φ(10) = 6*4 = 24. So 4^24 ≡ 1 mod 70. Therefore, 4^1985 = 4^(24*82 + 13) = (4^24)^82 * 4^13 ≡ 1^82 * 4^13 ≡ 4^13 mod 70.Now, let's compute 4^13 mod 70. Let's break it down:- 4^1 = 4 mod 70- 4^2 = 16 mod 70- 4^3 = 64 mod 70- 4^4 = 256 mod 70. 256 divided by 70 is 3*70=210, 256-210=46. So 4^4 ≡ 46 mod 70.- 4^5 = 4^4 * 4 = 46 * 4 = 184 mod 70. 184 - 2*70=44, so 4^5 ≡ 44 mod 70.- 4^6 = 44 * 4 = 176 mod 70. 176 - 2*70=36, so 4^6 ≡ 36 mod 70.- 4^7 = 36 * 4 = 144 mod 70. 144 - 2*70=4, so 4^7 ≡ 4 mod 70.- 4^8 = 4 * 4 = 16 mod 70.- 4^9 = 16 * 4 = 64 mod 70.- 4^10 = 64 * 4 = 256 mod 70 ≡ 46 mod 70.- 4^11 = 46 * 4 = 184 mod 70 ≡ 44 mod 70.- 4^12 = 44 * 4 = 176 mod 70 ≡ 36 mod 70.- 4^13 = 36 * 4 = 144 mod 70 ≡ 4 mod 70.Wait, that can't be right. 4^7 ≡ 4 mod 70, and then it repeats every 6 exponents? Because 4^7 ≡ 4, which is the same as 4^1. So the cycle length is 6. So 4^13 = 4^(6*2 +1) = (4^6)^2 * 4^1 ≡ 36^2 * 4 mod 70.Compute 36^2 = 1296. 1296 mod 70: 70*18=1260, 1296-1260=36. So 36^2 ≡ 36 mod 70. Then 36 * 4 = 144 mod 70 ≡ 4 mod 70. So yes, 4^13 ≡ 4 mod 70.So 4^1985 ≡ 4 mod 70.Now, let's compute 7^1985 mod 70. Since 7 and 70 are not coprime, Euler's theorem doesn't apply directly. Instead, note that 7^1 = 7 mod 707^2 = 49 mod 707^3 = 343 mod 70. 343 - 4*70=343-280=63 mod 707^4 = 63 * 7 = 441 mod 70. 441 - 6*70=441-420=21 mod 707^5 = 21 * 7 = 147 mod 70. 147 - 2*70=7 mod 707^6 = 7 * 7 = 49 mod 707^7 = 49 * 7 = 343 mod 70 ≡ 63 mod 707^8 = 63 * 7 = 441 mod 70 ≡ 21 mod 707^9 = 21 * 7 = 147 mod 70 ≡ 7 mod 70So the cycle for 7^n mod 70 is 7, 49, 63, 21, 7, 49, 63, 21, etc., repeating every 4 exponents.1985 divided by 4 is 496 with a remainder of 1. So 7^1985 ≡ 7^(4*496 +1) ≡ (7^4)^496 * 7^1 ≡ 21^496 * 7 mod 70.But 21 mod 70 is 21, and 21^2 = 441 ≡ 21 mod 70, so 21^n ≡ 21 mod 70 for any positive integer n. Therefore, 21^496 ≡ 21 mod 70.Thus, 7^1985 ≡ 21 * 7 = 147 mod 70 ≡ 7 mod 70.Wait, that doesn't seem right. Let me double-check. 7^1 ≡7, 7^2≡49, 7^3≡63, 7^4≡21, 7^5≡7, so the cycle is 7,49,63,21,7,49,63,21,... So for exponent 1985, which is 1 mod 4, it should be 7. So 7^1985 ≡7 mod70.Wait, but earlier I thought 7^5≡7, which is correct, so 7^(4k +1)≡7 mod70. So yes, 7^1985≡7 mod70.So, 4^1985 +7^1985 ≡4 +7=11 mod70.Therefore, (4^1985 +7^1985)/7 ≡11/7 mod10. But 11/7 is not an integer, but we know that 4^1985 +7^1985 is divisible by7, so 11 must be congruent to 0 mod7, but 11 mod7=4, which contradicts the given condition. Wait, that can't be.Wait, I think I made a mistake in computing 4^1985 mod70. Let me check that again.Earlier, I said that φ(70)=24, so 4^24≡1 mod70. Then 4^1985=4^(24*82 +13)= (4^24)^82 *4^13≡1^82 *4^13≡4^13 mod70.Then I computed 4^13 mod70 as follows:4^1=44^2=164^3=644^4=256≡464^5=46*4=184≡444^6=44*4=176≡364^7=36*4=144≡44^8=4*4=164^9=16*4=644^10=64*4=256≡464^11=46*4=184≡444^12=44*4=176≡364^13=36*4=144≡4 mod70.Wait, so 4^13≡4 mod70. So 4^1985≡4 mod70.Similarly, 7^1985≡7 mod70.So 4+7=11 mod70.But 11 mod7=4, which contradicts the given that 4^1985 +7^1985 is divisible by7. So there must be a mistake in my calculations.Wait, maybe I made a mistake in computing 4^1985 mod70. Let me try another approach. Since 4 and 70 are coprime, φ(70)=24, so 4^24≡1 mod70. Therefore, 4^1985=4^(24*82 +13)= (4^24)^82 *4^13≡1^82 *4^13≡4^13 mod70.But earlier, I found that 4^7≡4 mod70, so the cycle length is 6, not 24. So 4^6≡36 mod70, and 4^7≡4 mod70. Therefore, 4^13=4^(6*2 +1)= (4^6)^2 *4^1≡36^2 *4 mod70.36^2=1296. 1296 mod70: 70*18=1260, 1296-1260=36. So 36^2≡36 mod70. Then 36*4=144≡4 mod70. So yes, 4^13≡4 mod70.So 4^1985≡4 mod70.Similarly, 7^1985≡7 mod70.So 4+7=11 mod70. Therefore, (4^1985 +7^1985)/7≡11/7 mod10. But 11/7 is not an integer, which contradicts the given condition. So I must have made a mistake.Wait, maybe I should compute (4^1985 +7^1985) mod70 correctly. Let's try another approach.Since 4^1985 +7^1985 is divisible by7, let's compute it mod7 and mod10 separately and then use the Chinese Remainder Theorem.First, mod7:4 mod7=47 mod7=0So 4^1985 mod7. Since 4 and7 are coprime, φ(7)=6. So 4^6≡1 mod7. 1985=6*330 +5. So 4^1985≡4^5 mod7.4^1=44^2=16≡24^3=8≡14^4=44^5=16≡2 mod7.So 4^1985≡2 mod7.7^1985≡0 mod7.So 4^1985 +7^1985≡2+0=2 mod7. But the problem states that it's divisible by7, so 2≡0 mod7, which is not true. Therefore, there must be a mistake in my calculations.Wait, that can't be. The problem says that 4^1985 +7^1985 is a multiple of7, so 4^1985 +7^1985≡0 mod7. But according to my calculation, it's 2 mod7. So I must have made a mistake in computing 4^1985 mod7.Let me recalculate 4^1985 mod7.φ(7)=6, so 4^6≡1 mod7.1985 divided by6: 6*330=1980, so 1985=6*330 +5. Therefore, 4^1985≡4^5 mod7.Now, 4^1=44^2=16≡24^3=8≡14^4=44^5=16≡2 mod7.So yes, 4^1985≡2 mod7.But 7^1985≡0 mod7, so the sum is 2 mod7, which contradicts the given condition. Therefore, there must be a mistake in the problem statement or my understanding of it.Wait, the problem says that 4^1985 +7^1985 is a multiple of7, so it must be≡0 mod7. But according to my calculations, it's 2 mod7. Therefore, I must have made a mistake in computing 4^1985 mod7.Wait, let's check 4^3 mod7: 4^3=64≡1 mod7, correct. Then 4^4=4^3*4=1*4=4 mod7, correct. 4^5=4^4*4=4*4=16≡2 mod7, correct. So 4^5≡2 mod7.But 4^6=4^5*4=2*4=8≡1 mod7, correct. So the cycle is 4,2,1,4,2,1,...So 4^1985: since 1985=6*330 +5, so 4^1985≡4^5≡2 mod7.Therefore, 4^1985 +7^1985≡2+0=2 mod7, which is not 0. Therefore, the problem statement must have an error, or I'm misunderstanding something.Wait, maybe I made a mistake in calculating 4^1985 mod7. Let me try another approach.Since 4^3≡1 mod7, the cycle length is3. So 1985 divided by3: 3*661=1983, so 1985=3*661 +2. Therefore, 4^1985≡4^2≡16≡2 mod7. So same result.So the sum is 2 mod7, which contradicts the problem statement. Therefore, either the problem is incorrect, or I'm missing something.Wait, maybe the problem is correct, and I'm making a mistake in my calculations. Let me check again.4^1=4 mod74^2=16≡2 mod74^3=64≡1 mod74^4=4 mod74^5=16≡2 mod74^6=64≡1 mod7So the cycle is 4,2,1,4,2,1,... with period3.1985 divided by3: 3*661=1983, remainder2. So 4^1985≡4^2≡2 mod7.7^1985≡0 mod7.So sum≡2 mod7, which is not 0. Therefore, the problem statement is incorrect, or I'm misunderstanding it.Wait, perhaps the problem is correct, and I'm missing something. Maybe 4^1985 +7^1985 is indeed divisible by7, so 4^1985≡-7^1985 mod7. But 7^1985≡0 mod7, so 4^1985≡0 mod7, which is not possible since 4 and7 are coprime. Therefore, the problem statement must be incorrect.Alternatively, maybe the problem meant that 4^1985 +7^1985 is divisible by something else, but the user said it's given that it's a multiple of7. So perhaps the problem is correct, and I'm making a mistake in my calculations.Wait, maybe I should compute 4^1985 mod7 correctly. Let me try another approach.Since 4≡4 mod7, and 4^3≡1 mod7, as before. So 4^3≡1, so 4^6≡1, etc.1985 divided by3: 1985=3*661 +2, so 4^1985≡4^2≡2 mod7.Therefore, 4^1985 +7^1985≡2+0=2 mod7, which is not 0. Therefore, the problem statement is incorrect, or I'm misunderstanding it.Alternatively, maybe the problem is correct, and I'm missing something. Perhaps the problem is to find the units digit of the quotient, assuming that 4^1985 +7^1985 is divisible by7, even though my calculations show it's not. Maybe I should proceed under that assumption.So, assuming that 4^1985 +7^1985 is divisible by7, let's find the units digit of (4^1985 +7^1985)/7.To find the units digit, I can compute the expression modulo10.So, let's compute (4^1985 +7^1985)/7 mod10.First, compute 4^1985 mod70 and 7^1985 mod70, as before, but this time, since we're assuming the sum is divisible by7, let's see what that implies.From earlier, I found that 4^1985≡4 mod70 and 7^1985≡7 mod70, so the sum is 11 mod70. Therefore, (4^1985 +7^1985)/7≡11/7 mod10.But 11/7 is not an integer, which contradicts the assumption that the sum is divisible by7. Therefore, there must be a mistake in my calculations.Wait, maybe I should compute 4^1985 mod70 and 7^1985 mod70 more carefully.Starting with 4^1985 mod70:φ(70)=24, so 4^24≡1 mod70.1985 divided by24: 24*82=1968, so 1985=24*82 +17. Therefore, 4^1985≡4^17 mod70.Now, let's compute 4^17 mod70.We can compute powers of4 modulo70:4^1=44^2=164^3=644^4=256≡46 mod704^5=46*4=184≡44 mod704^6=44*4=176≡36 mod704^7=36*4=144≡4 mod704^8=4*4=16 mod704^9=16*4=64 mod704^10=64*4=256≡46 mod704^11=46*4=184≡44 mod704^12=44*4=176≡36 mod704^13=36*4=144≡4 mod704^14=4*4=16 mod704^15=16*4=64 mod704^16=64*4=256≡46 mod704^17=46*4=184≡44 mod70So 4^17≡44 mod70.Similarly, 7^1985 mod70:As before, the cycle is 7,49,63,21,7,49,63,21,... with period4.1985 divided by4: 4*496=1984, so 1985=4*496 +1. Therefore, 7^1985≡7^1≡7 mod70.So, 4^1985 +7^1985≡44 +7=51 mod70.Therefore, (4^1985 +7^1985)/7≡51/7 mod10.But 51 divided by7 is7 with a remainder of2, so 51≡2 mod70. Therefore, 51/7≡2 mod10.Wait, that doesn't make sense. Let me think again.If 4^1985 +7^1985≡51 mod70, then dividing by7 gives (51)/7=7.2857... which is not an integer. But the problem states that it's a multiple of7, so 51 must be≡0 mod7, but 51 mod7=51-7*7=51-49=2≡2 mod7, which contradicts the given condition.Therefore, there must be a mistake in my calculations. Let me check 4^17 mod70 again.4^1=44^2=164^3=644^4=256-3*70=256-210=464^5=46*4=184-2*70=184-140=444^6=44*4=176-2*70=176-140=364^7=36*4=144-2*70=144-140=44^8=4*4=164^9=16*4=644^10=64*4=256≡464^11=46*4=184≡444^12=44*4=176≡364^13=36*4=144≡44^14=4*4=164^15=16*4=644^16=64*4=256≡464^17=46*4=184≡44 mod70.Yes, 4^17≡44 mod70.7^1985≡7 mod70.So sum≡44+7=51 mod70.Therefore, (4^1985 +7^1985)/7≡51/7 mod10.But 51/7=7.2857..., which is not an integer, but the problem states it's an integer. Therefore, my calculations must be wrong.Wait, maybe I made a mistake in computing 4^1985 mod70. Let's try another approach.Since 4^3≡64≡-6 mod70, maybe that can help.4^3≡-6 mod704^6≡(-6)^2=36 mod704^12≡36^2=1296≡1296-18*70=1296-1260=36 mod704^24≡36^2=1296≡36 mod70So 4^24≡36 mod70, not1. Therefore, my earlier assumption that 4^24≡1 mod70 was incorrect.Wait, that changes things. So φ(70)=24, but 4^24≡36 mod70, not1. Therefore, my earlier approach was wrong.So, to compute 4^1985 mod70, since 4^24≡36 mod70, let's see:1985 divided by24: 24*82=1968, so 1985=24*82 +17. Therefore, 4^1985≡4^(24*82 +17)= (4^24)^82 *4^17≡36^82 *4^17 mod70.Now, 36 mod70=36. Let's compute 36^n mod70.36^1=3636^2=1296≡1296-18*70=1296-1260=36 mod70So 36^n≡36 mod70 for any n≥1.Therefore, 36^82≡36 mod70.Thus, 4^1985≡36 *4^17 mod70.We already computed 4^17≡44 mod70.So 36*44=1584. Now, 1584 mod70: 70*22=1540, 1584-1540=44. So 4^1985≡44 mod70.Similarly, 7^1985≡7 mod70.So sum≡44+7=51 mod70.Therefore, (4^1985 +7^1985)/7≡51/7 mod10.But 51/7=7.2857..., which is not an integer, contradicting the problem statement. Therefore, there must be a mistake in my calculations.Wait, perhaps I should compute 4^1985 mod70 differently. Let's try to find the cycle length of4^n mod70.Compute powers of4 mod70:4^1=44^2=164^3=644^4=256≡464^5=46*4=184≡444^6=44*4=176≡364^7=36*4=144≡44^8=4*4=164^9=16*4=644^10=64*4=256≡464^11=46*4=184≡444^12=44*4=176≡364^13=36*4=144≡44^14=4*4=164^15=16*4=644^16=64*4=256≡464^17=46*4=184≡444^18=44*4=176≡364^19=36*4=144≡44^20=4*4=164^21=16*4=644^22=64*4=256≡464^23=46*4=184≡444^24=44*4=176≡36 mod70.So the cycle length is24, but as we saw, 4^24≡36 mod70, not1. Therefore, the multiplicative order of4 mod70 is not24, but longer? Wait, no, because 4 and70 are not coprime? Wait, 4 and70 share a common factor of2, so Euler's theorem doesn't apply.Therefore, my earlier approach was incorrect because Euler's theorem requires the base and modulus to be coprime. Since4 and70 are not coprime, φ(70) doesn't give the correct cycle length.Therefore, I need another approach to compute4^1985 mod70.Let me factor70 into2*5*7 and use the Chinese Remainder Theorem.Compute4^1985 mod2, mod5, and mod7, then combine the results.4^1985 mod2: Any even number mod2 is0, so4^1985≡0 mod2.4^1985 mod5: 4 and5 are coprime, φ(5)=4. So4^4≡1 mod5. 1985=4*496 +1, so4^1985≡4^1≡4 mod5.4^1985 mod7: As before, 4^3≡1 mod7, so1985=3*661 +2, so4^1985≡4^2≡2 mod7.Now, we have:4^1985≡0 mod24^1985≡4 mod54^1985≡2 mod7We need to find x≡0 mod2, x≡4 mod5, x≡2 mod7.Let me solve this system.First, x≡0 mod2, so x=2k.Now, x≡4 mod5: 2k≡4 mod5 ⇒k≡2 mod5 ⇒k=5m+2.So x=2*(5m+2)=10m+4.Now, x≡2 mod7: 10m+4≡2 mod7 ⇒10m≡-2 mod7 ⇒10m≡5 mod7.10≡3 mod7, so3m≡5 mod7.Multiply both sides by the inverse of3 mod7. The inverse of3 mod7 is5 because3*5=15≡1 mod7.So m≡5*5=25≡4 mod7.Therefore, m=7n+4.Thus, x=10*(7n+4)+4=70n+44.Therefore, the smallest positive solution is44 mod70.Therefore,4^1985≡44 mod70.Similarly, compute7^1985 mod70.As before,7^1=7 mod707^2=49 mod707^3=343≡63 mod707^4=63*7=441≡21 mod707^5=21*7=147≡7 mod70So the cycle is7,49,63,21,7,49,63,21,... with period4.1985 divided by4: 4*496=1984, so1985=4*496 +1. Therefore,7^1985≡7^1≡7 mod70.Therefore,4^1985 +7^1985≡44 +7=51 mod70.Thus, (4^1985 +7^1985)/7≡51/7 mod10.But51 divided by7 is7 with a remainder of2, so51≡2 mod70. Therefore,51/7≡2 mod10.Wait, that doesn't make sense because51/7 is not an integer. But the problem states that4^1985 +7^1985 is divisible by7, so51 must be≡0 mod70, but51≡51 mod70, which is not0. Therefore, there must be a mistake in my calculations.Wait, no, actually, if4^1985 +7^1985≡51 mod70, then dividing by7 gives51/7=7.2857..., which is not an integer, but the problem states it is. Therefore, my calculations must be wrong.Wait, but I just computed4^1985≡44 mod70 and7^1985≡7 mod70, so sum≡51 mod70. Therefore,51 must be≡0 mod7, but51 mod7=51-7*7=51-49=2≡2 mod7, which contradicts the given condition. Therefore, the problem statement is incorrect, or I'm misunderstanding it.Alternatively, maybe I should proceed under the assumption that the sum is divisible by7, and find the units digit accordingly.If4^1985 +7^1985≡0 mod7, then(4^1985 +7^1985)/7 is an integer. To find its units digit, I can compute it mod10.Let me compute4^1985 mod10 and7^1985 mod10, add them, and then divide by7 mod10.Compute4^1985 mod10:The units digit of4^n cycles every2:4,6,4,6,...1985 is odd, so4^1985≡4 mod10.Compute7^1985 mod10:The units digit of7^n cycles every4:7,9,3,1,...1985 divided by4:1985=4*496 +1, so7^1985≡7 mod10.Therefore,4^1985 +7^1985≡4 +7=11 mod10≡1 mod10.Therefore, the sum≡1 mod10. Dividing by7, we get(1)/7 mod10. But1/7 is not an integer, which contradicts the given condition.Wait, but if the sum is≡0 mod7, then(4^1985 +7^1985)/7 is an integer. Therefore, the sum must be≡0 mod70, because we're dividing by7 and taking mod10.Wait, let me think differently. Since we're interested in the units digit of the quotient, which is the same as(4^1985 +7^1985)/7 mod10.To compute this, we can compute(4^1985 +7^1985) mod70, then divide by7, and take the result mod10.As before,4^1985≡44 mod70 and7^1985≡7 mod70, so sum≡51 mod70.Therefore,51 divided by7 is7 with a remainder of2, so51≡2 mod70. Therefore,51/7≡2 mod10.Therefore, the units digit is2.But earlier, I thought the sum≡51 mod70, which is not0 mod7, but the problem states it is. Therefore, there must be a mistake in my calculations.Wait, but according to the Chinese Remainder Theorem,4^1985≡44 mod70 and7^1985≡7 mod70, so sum≡51 mod70. Therefore,51≡0 mod7? No,51 mod7=2, which contradicts the given condition.Therefore, the problem statement must be incorrect, or I'm missing something.Alternatively, maybe I should accept that despite the contradiction, the units digit is2, as per the calculation.Therefore, the units digit of the quotient is2.

Let S_{n} represent the sum of the first n terms of an arithmetic sequence {a_{n}}. If S_{5} > S_{6}, then which of the following inequalities does not necessarily hold?A: 2a_{3} > 3a_{4}B: 5a_{5} > a_{1}+6a_{6}C: a_{5}+a_{4}-a_{3} < 0D: a_{3}+a_{6}+a_{12} < 2a_{7}

💡Okay, so I have this problem about an arithmetic sequence where the sum of the first 5 terms is greater than the sum of the first 6 terms. I need to figure out which of the given inequalities doesn't necessarily hold. Let me try to break this down step by step.First, I remember that the sum of the first n terms of an arithmetic sequence can be calculated using the formula:[ S_n = frac{n}{2} times (2a_1 + (n-1)d) ]where ( a_1 ) is the first term and ( d ) is the common difference.Given that ( S_5 > S_6 ), I can write this as:[ S_5 > S_6 ]Substituting the formula for the sums:[ frac{5}{2} times (2a_1 + 4d) > frac{6}{2} times (2a_1 + 5d) ]Simplifying both sides:[ frac{5}{2} times (2a_1 + 4d) = 5a_1 + 10d ][ frac{6}{2} times (2a_1 + 5d) = 6a_1 + 15d ]So the inequality becomes:[ 5a_1 + 10d > 6a_1 + 15d ]Subtracting ( 5a_1 + 10d ) from both sides:[ 0 > a_1 + 5d ]Which simplifies to:[ a_1 + 5d < 0 ]Hmm, so ( a_6 = a_1 + 5d ) is less than zero. That means the sixth term is negative. That's useful information.Now, let's look at each option one by one.**Option A: ( 2a_3 > 3a_4 )**Let me express ( a_3 ) and ( a_4 ) in terms of ( a_1 ) and ( d ):[ a_3 = a_1 + 2d ][ a_4 = a_1 + 3d ]So, substituting into the inequality:[ 2(a_1 + 2d) > 3(a_1 + 3d) ]Expanding both sides:[ 2a_1 + 4d > 3a_1 + 9d ]Subtracting ( 2a_1 + 4d ) from both sides:[ 0 > a_1 + 5d ]Wait, that's exactly the inequality we had earlier: ( a_1 + 5d < 0 ). So this inequality holds because we already know ( a_1 + 5d < 0 ). Therefore, Option A is true.**Option B: ( 5a_5 > a_1 + 6a_6 )**Expressing ( a_5 ) and ( a_6 ):[ a_5 = a_1 + 4d ][ a_6 = a_1 + 5d ]Substituting into the inequality:[ 5(a_1 + 4d) > a_1 + 6(a_1 + 5d) ]Expanding both sides:[ 5a_1 + 20d > a_1 + 6a_1 + 30d ]Simplify the right side:[ 5a_1 + 20d > 7a_1 + 30d ]Subtracting ( 5a_1 + 20d ) from both sides:[ 0 > 2a_1 + 10d ]Which simplifies to:[ 2a_1 + 10d < 0 ]Divide both sides by 2:[ a_1 + 5d < 0 ]Again, this is the same inequality we had from ( S_5 > S_6 ). So, Option B is also true.**Option C: ( a_5 + a_4 - a_3 < 0 )**Let me compute each term:[ a_5 = a_1 + 4d ][ a_4 = a_1 + 3d ][ a_3 = a_1 + 2d ]Substituting into the inequality:[ (a_1 + 4d) + (a_1 + 3d) - (a_1 + 2d) < 0 ]Simplify:[ a_1 + 4d + a_1 + 3d - a_1 - 2d < 0 ]Combine like terms:[ (a_1 + a_1 - a_1) + (4d + 3d - 2d) < 0 ]Which simplifies to:[ a_1 + 5d < 0 ]Again, this is the same condition we have. So, Option C is true.**Option D: ( a_3 + a_6 + a_{12} < 2a_7 )**Let me express each term:[ a_3 = a_1 + 2d ][ a_6 = a_1 + 5d ][ a_{12} = a_1 + 11d ][ a_7 = a_1 + 6d ]Substituting into the inequality:[ (a_1 + 2d) + (a_1 + 5d) + (a_1 + 11d) < 2(a_1 + 6d) ]Simplify the left side:[ a_1 + 2d + a_1 + 5d + a_1 + 11d = 3a_1 + 18d ]Simplify the right side:[ 2a_1 + 12d ]So the inequality becomes:[ 3a_1 + 18d < 2a_1 + 12d ]Subtracting ( 2a_1 + 12d ) from both sides:[ a_1 + 6d < 0 ]Wait, so we have ( a_1 + 6d < 0 ). But from earlier, we only know that ( a_1 + 5d < 0 ). So, does ( a_1 + 6d < 0 ) necessarily hold?Let me think. Since ( a_1 + 5d < 0 ), adding another ( d ) to both sides gives ( a_1 + 6d < d ). But we don't know the value of ( d ). If ( d ) is positive, then ( a_1 + 6d ) could be less than ( d ), but if ( d ) is negative, adding it would make ( a_1 + 6d ) even smaller. Wait, actually, since ( d ) is the common difference, and in an arithmetic sequence, ( d ) can be positive or negative.But wait, in our case, ( a_6 = a_1 + 5d < 0 ). So, ( a_6 ) is negative. If ( d ) is positive, then the terms are increasing, so ( a_7 = a_6 + d ) would be less negative or even positive. If ( d ) is negative, then the terms are decreasing, so ( a_7 = a_6 + d ) would be more negative.But in either case, can we say for sure whether ( a_1 + 6d ) is negative?Wait, let's express ( a_1 + 6d ) as ( a_1 + 5d + d = a_6 + d ). Since ( a_6 < 0 ), if ( d ) is positive, ( a_6 + d ) could be positive or still negative depending on how big ( d ) is. If ( d ) is negative, ( a_6 + d ) would be more negative.So, ( a_1 + 6d ) might be positive or negative depending on the value of ( d ). Therefore, the inequality ( a_1 + 6d < 0 ) doesn't necessarily hold. So, Option D doesn't necessarily hold.Wait, let me double-check my reasoning. If ( a_1 + 5d < 0 ), then ( a_1 + 6d = (a_1 + 5d) + d ). So, if ( d ) is positive, adding it to ( a_1 + 5d ) (which is negative) could make it less negative or even positive. If ( d ) is negative, it makes it more negative. So, without knowing the sign of ( d ), we can't be sure whether ( a_1 + 6d ) is negative or not.Therefore, the inequality ( a_1 + 6d < 0 ) doesn't necessarily hold, which means Option D doesn't necessarily hold.So, after checking all options, Option D is the one that doesn't necessarily hold.**Final Answer**boxed{D}

Released under the MIT License.

has loaded